2022
DOI: 10.3390/su14042322
|View full text |Cite
|
Sign up to set email alerts
|

Global Drivers for ESG Performance: The Body of Knowledge

Abstract: Progress on Environmental, Social and Governance (ESG) issues is vastly different depending where in the world you look. However, the literature on what drives ESG performance is highly fragmented and current theories fail to offer useful insights into the disparity in ESG performance. Hence, this study draws upon an accumulated body of knowledge of ESG-related literature and explores the major drivers of ESG performance. By applying a scientific and replicable methodology of systematic literature review, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 78 publications
(102 reference statements)
3
23
0
Order By: Relevance
“…Second, interviewees identified company location as a factor driving differences in measure implementation maturity. This finding is in line with previous research on sustainability advancements globally, which suggests that ESG performance varies among geographic regions (Daugaard & Ding, 2022). While Europe is the leading region in terms of ESG performance globally, eastern Europe lags behind western Europe, and among western European countries, France, Spain, Portugal, Finland, and Sweden clearly outperform Germany (Daugaard & Ding, 2022).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Second, interviewees identified company location as a factor driving differences in measure implementation maturity. This finding is in line with previous research on sustainability advancements globally, which suggests that ESG performance varies among geographic regions (Daugaard & Ding, 2022). While Europe is the leading region in terms of ESG performance globally, eastern Europe lags behind western Europe, and among western European countries, France, Spain, Portugal, Finland, and Sweden clearly outperform Germany (Daugaard & Ding, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…First, we found that publicly traded companies reach higher target-setting maturity than family-owned or otherwise privately-owned companies and that larger companies reach higher maturity than smaller ones. These findings are supported by previous research that suggests that reporting requirements can impact the ESG focus of companies (Leong & Hazelton, 2019) (Daugaard & Ding, 2022).…”
Section: Theoretical Contributionssupporting
confidence: 88%
See 1 more Smart Citation
“…This paper suggests that governments with poor financial capacity, they can still mobilize social forces to participate in environmental governance. For example, governments can propagate and promote the application of ESG (Environmental, Social and Governance) which is an investment concept and evaluation standard that focuses on enterprise environment, society and governance performance rather than financial performance (Daugaard and Ding, 2022). ESG will encourage companies to increase investment on air protection and alleviate the increasing pressure of government environmental investment.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of these groups of factors, which have been brought together under the abbreviation ESG, has been actively studied in relation to various economic features and processes at the micro-, macro-, and meso-economic levels. As a result, reviews and meta-analyses of the literature have already appeared, revealing the conceptual foundations of ESG factors (see, for example, Daugaard and Ding, 2022), their taxonomy, and approximating indicators (Li et al, 2021 andWidyawati, 2020), the impact on company performance (Huang, 2021), and the pricing and risks of various assets (Campiglio et al, 2022).…”
Section: Introductionmentioning
confidence: 99%